Design, Synthesis and Radioprotective Activity Evaluation of Novel N-Phenyl-2H-chromene-3-carboxamides Derived from Ex-RAD - Liu, Xin-Ru; Feng, Han-Yin; Liu, Xiao-Han; Xu, Jing; Liu, Shu-Chen; Zhang, Shou-Guo; Peng, Tao (Chemical & pharmaceutical bulletin, 2025)
Exposures to ionizing radiation can cause serious damages to human body, and the development of radiation countermeasures is urgently needed. In this paper, a series of N-phenyl-2H-chromene-3-carboxamides were designed and synthesized as potential radiation countermeasures. Their radioprotective activities were evaluated in vitro and in vivo, and compound B5 was identified as the most effective molecule among the target compounds. B5 can not only accelerate the recovery of peripheral blood cells in mice exposed to total body irradiation, but also alleviate damage to the small intestine, spleen and thymus in mice exposed to abdominal irradiation. Furthermore, B5 exhibited superior ability to mitigate radiation-induced DNA damage and apoptosis in irradiated AHH-1 cells. Western blot analysis indicated that the radioprotection provided by B5 resulted in the downregulation of pro-apoptosis proteins p53 and upregulation of anti-apoptosis protein Bcl-2. In addition, the RNA-Sequencing analysis revealed that B5 primarily exerts its radioprotective effects through the Wnt signaling pathway and the mitogen-activated protein kinase (MAPK) signaling pathway. In conclusion, we identified B5 as a promising radioprotective compound, and B5 is valuable for further research in the future.